The Effect of ginger essential oil (Zingiber Officinale) as repellent towards Aedes aegypti - Ery Agus Mardiansyah; Sitti Rahmah Umniyati; Susi Iravati (Berita Kedokteran Masyarakat (BKM), 2016)
The effect of ginger essential oil (Zingiber officinale) as an effective repellent  against the Aedes aegypti mosquitoPurposeThe purpose of this paper was to determine the ability of ginger essential oil (Zingiber officinale) as a repellent towards Aedes aegypti. MethodsThis research was a true experimental study. The tests performed in this study were negative control tests, with protective ability test of telon plus oil and ginger essential oil 4% in telon oil involving 25 Aedes aegypti adult female mosquitoes. ResultsThe study found that the average protective ability of ginger essential oil 4 % in telon oil was 100% at minute 5, 10, and 15, while telon oil plus (positive control) was 5%, 36%, and 33%. In the protective ability test of ginger essential oil 4% in telon oil has the better repellent ability or protective ability compared to telon plus, which can provide protective ability up to 60 minutes at 91.95% while telon plus oil provides protective ability around 59.51%. In the length of protection test ginger essential oil 4% in telon oil gave an average of protection from biting until 61.67 minutes, while telon oil gives 8.33 minutes and 11.67 minutes of telon plus oil. Based on Probit analysis ginger essential oil 4% in telon oil can repel 90% of experimental mosquitoes up to 89.87 minutes. ConclusionGinger essential oil 4% in telon oil has the better repellent ability and length of protection compared to telon plus oil. Ginger essential oil 4% in telon can be used as a repellent active ingredient.